Improving PCK of chemical equilibrium in pre-service teachers - Mavhunga, Elizabeth; Rollnick, Marissa (Routledge, 2013)
It is commonly accepted that Pedagogical Content Knowledge (PCK) has a topic-specific nature. However, its implementation in teacher education programmes has remained generic and tacit. This paper reports on an attempt to improve the quality of PCK in chemistry pre service teachers in a specified topic—chemical equilibrium. By locating PCK at a topic level, a refined theoretical description of the construct sensitive to the specificity of the topic is suggested and its validity argued. The refined description is grounded on the notion of transformation of topic-specific concepts to PCK, and the identification of components that enable such a transformation. The components were identified as Learners’ Prior Knowledge, Curricular Saliency, What makes a topic easy or difficult to understand, Representations including analogies and Conceptual Teaching Strategies. The extent to which the explicit teaching of these five components influences the improvement of the quality of PCK within Chemical Equilibrium was determined in an intervention with 16 physical science pre-service teachers. The impact of the intervention was determined through mixed methods. The intervention resulted in a significant (99% confidence) overall improvement of the quality of PCK within chemical equilibrium. The findings signal a reciprocal relationship between PCK and the pedagogical transformation of concepts, where the latter was previously reported to result from PCK. Recommendations with regard to constructing PCK at a topic level in teacher education programmes are suggested with particular reference to the South African context.
Keywords: Science teaching – pedagogical content knowledge; Topic-specific PCK; Chemical equilibrium – study and teaching – South Africa; Chemical equilibrium – transformation of concepts to PCK